Consequences of Bt Cotton Technology Importation - Rola, Agnes C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
The article discusses the results of an ex-ante assessment of the consequences of importation of Bt cotton tolerant to cotton bollworm and pink bollworm in order to guide policy decisions on whether or not to import and commercialize the technology in the Philippines. Primary and secondary data were generated through farm survey, interviews of key informants from the public and the private sectors, and focus group discussions with stakeholders. Four components of ex-ante assessment were done: industry level, location-specific research and development, commercialization and farm-level adoption. Welfare analysis was also conducted. Based on the results, importation could only be economically viable if the land area planted to Bt cotton is greater than 5,000 ha, a little higher than the 3,681 ha planted to traditional cotton for the crop year 2005-2006. Commercialization of Bt cotton in the Philippines will also result in positive benefits if the spill-over effects are taken into account, if regulatory costs are reasonable and if a yield increase of at least 20% is realized by farmers. The introduction of Bt cotton in the Philippines could broaden the farmers' technology base. With the high level of expected benefits, the private sector can be attracted to invest in its commercialization. Reduced regulatory costs could actually translate to lower seed costs, thereby, promoting farmer adoption. If the technology is made available in the country, government should be vigilant in monitoring its possible environmental impacts and that of all other Bt and genetically modified (GM) crops for feedback to researchers and regulators and for risk reduction strategies.